Pengaruh Pendidikan Kewirausahaan, dan Efikasi Diri terhadap Intensi Berwirausaha dengan Motivasi Berwirausaha sebagai Variabel Mediasi - Hansen Andrianto; Oey Hannes Widjaja (EduInovasi: Journal of Basic Educational Studies, 2025)
This study aims to examine the influence of entrepreneurship education and self-efficacy on entrepreneurial intention, with entrepreneurial motivation as a mediating variable among Generation Z. This research employs a descriptive research design with a quantitative approach. The data were collected through online qustionnaires using non- probability smapling and purposive sampling techniques. The population in this study consists of Generation Z individuals who have received entrepreneurship education. The data analysis technique used was PLS-SEM with the SmartPLS 4 software.The results of this research show that: a) entrepreneurship education has a positive and significant effect on entrepreneurial intention; b) self-efficacy has a positive and insignificant effect on entrepreneurial intention; c) entrepreneurial motivation has a positive and significant effect on entrepreneurial intention; d) entrepreneurship education has a positive and significant effect on entrepreneurial motivation; e) self- efficacy has a positive and significant effect on entrepreneurial motivation; f) entrepreneurial motivation is not able to mediate the relationship between entrepreneurship education and entrepreneurial intention; g) entrepreneurial motivation is able to mediate the relationship between self-efficacy and entrepreneurial intention.